Assessing the synergies of the water–economy–ecology nexus in resource-based cities: a case study of Shaanxi, China - Cheng, Zhe; Ding, Bowen; Ma, Li (Frontiers in Sustainable Cities, 2025)
IntroductionUnderstanding the synergies and trade-off between the economy, ecological environment, and water resources is crucial to realizing the transformation and sustainable development of resource-based cities (RBCs).MethodsIn order to identify and evaluate the situation, spatio-temporal characteristics, and impact factors of the regional water–economy–ecology (WEE) nexus, this study builds an evaluation indicators system of coupling coordinated development for the WEE nexus, and employs multiple methods including spatial analysis and the Tobit model. Panel data from 2010 to 2021 of six RBCs in Shaanxi, China are the basis for this study.Results and discussionThe results show that RBCs in Shaanxi have seen an overall upward trend in the development of their water economies and environments in recent years. The fundamental issue facing RBCs in Shaanxi is uneven and inadequate development. The coupling coordination levels of RBCs have increased, albeit at varying rates, and most are in the primary coordination stage. The ecological environment, industrial structure, scientific and technical innovation, economic development, and industrial structure are all beneficial; the urbanization rate, however, has not met the significance test. This study adds to the knowledge body regarding the development of RBCs worldwide and aids scholars and practitioners in understanding the development of RBCs in China.